Validation of the mixed multifactor scale of educational engagement (MMSEE) - Colás-Bravo, Pilar; Reyes-de-Cózar, Salvador; Conde-Jiménez, Jesús (Anales de Psicología / Annals of Psychology, 2021)
Today, educational engagement is considered one of the most important factors in predicting good student learning and educational success. However, most of the instruments described do not include all the key factors linked to academic engagement: motivations, values, learning contexts, emotional state and management strategies. The aim of this study is to develop a scale to assess the level of educational engagement in Higher Education students (MMSEE) that overcomes this limitation. Methods: Exploratory and confirmatory factorial analyses, as well as a study of internal consistency, convergent and discriminant validity, were carried out on a sample of 764 students from the University of Seville (Spain), belonging to all areas of knowledge and different degree courses. Results: A multifactorial structure of educational engagement with five factors that explain a variance close to 65.78%, with an excellent internal consistency (α = .91) and with significant indicators of convergent and discriminant validity is explored and confirmed with a very good level of adjustment. Conclusions: It is concluded that MMSEE is a valid and reliable instrument to measure the level of engagement of classrooms, as well as to improve the understanding of the construct through its factors.